Developing pre-service teachers’ adaptive expertise through STEM-CT integration in professional development and residency placements - Moran, Renee M. R.; Robertson, Laura; Tai, Chihche; Ward, Natalia A.; Price, Jamie (Frontiers in Education, 2023)
This paper focuses on how one innovative teacher education model, that included a unique residency model and the integration of computational thinking and digital teaching and learning in elementary classrooms, supported the development of adaptive expertise in pre-service teacher education programs. The theoretical frame applied in this study is adaptive expertise through the lens of sociocultural theory, and it employs tenets of ethnographic research procedure as methodology. Data demonstrated that the model provided pre-service teachers with a rigorous setting that allowed for practice of routine expertise as well as adaptive expertise. Additionally, analysis pointed to balancing efficiency and innovation and mentor-mentee collaboration as key components of the development of adaptive expertise in pre-service teachers.